Client-side versus server-side geographic data processing performance comparison: Data and code - Kulawiak, Marcin (Data in brief, 2019)
The data and code presented in this article are related to the research article entitled “Analysis of Server-side and Client-side Web-GIS data processing methods on the example of JTS and JSTS using open data from OSM and Geoportal” (Kulawiak et al., 2019). The provided 12 datasets include multi-point and multi-polygon data of different scales and volumes, representing real-world geographic features. The datasets cover the area of Tricity in northern Poland as well as Polish Exclusive Economic Zone of the Baltic Sea. They have been converted to a common Spherical Mercator projection coordinate system (EPSG:3857) and consist of vector features without attributes. They are provided in the form of single GeoJSON files containing multi-feature objects which can be processed by client-side as well as server-side algorithms in a single request. The provided javascript code exemplifies the application of those datasets for measurement of client-side and server-side geoprocessing performance by using algorithms implemented as part of Java Topology Suite (JTS) and Javascript Topology Suite (JSTS). The combination of data and code samples constitutes a universal benchmark for investigative analysis of geographic data processing algorithms and their implementations in different software system architectures.